1983
DOI: 10.1021/bi00288a026
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of nucleotides opposite apurinic apyrimidinic sites in deoxyribonucleic acid during in vitro synthesis: uniqueness of adenine nucleotides

Abstract: M13 DNA containing 20-30 apurinic/apyrimidinic (AP) sites per intact circular molecule was prepared by growing phage on an ung- dut- Escherichia coli mutant and treating the DNA with uracil N-glycosylase. AP sites obstruct in vitro DNA synthesis catalyzed by E. coli pol I. The position at which termination of synthesis occurs was determined for four enzymes. T4 DNA polymerase terminates one nucleotide before putative AP sites. DNA pol I, AMV reverse transcriptase, and DNA polymerase alpha terminate synthesis e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
208
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(224 citation statements)
references
References 29 publications
12
208
1
3
Order By: Relevance
“…Both G:C to A:T transitions and G:C to T:A transversions leading to rifampicin resistance were observed in AGT-mediated response to DBE (Table I). The G to T transversions, which represent 20% of the mutations we observed in the rpoB gene are consistent with depurination of the Gua adduct and subsequent processing of the abasic site (46,47). However, in both the rpoB and the lacI genes, the most common mutations were G to A transitions.…”
Section: Discussionsupporting
confidence: 76%
“…Both G:C to A:T transitions and G:C to T:A transversions leading to rifampicin resistance were observed in AGT-mediated response to DBE (Table I). The G to T transversions, which represent 20% of the mutations we observed in the rpoB gene are consistent with depurination of the Gua adduct and subsequent processing of the abasic site (46,47). However, in both the rpoB and the lacI genes, the most common mutations were G to A transitions.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, the intermediate AP sites and SSB generated in this pathway are more cytotoxic in many cases than the modified base lesions themselves (Chaudhry and Weinfeld, 1997;Lockhart et al, 1982;Loeb and Preston, 1986;Sagher and Strauss, 1983;Schaaper et al, 1983;Whitehouse et al, 2001). MNU was used in the present studies to generate alkylation damage.…”
Section: Discussionmentioning
confidence: 99%
“…S1) have shown that purines, in particular adenosine, and to a lesser extent guanosine, are most frequently incorporated opposite the lesion. The strong preference for adenosine has been termed "A-rule" (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%